Japan 1941 eaudiobook Countdown to infamy. - Hotta, Eri (Tantor Media, 2013)
When Japan attacked the United States in 1941, argues Eri Hotta, its leaders, in large part, understood they were entering a conflict they were bound to lose. Availing herself of rarely consulted material, Hotta poses essential questions overlooked by historians in the seventy years since: Why did these men—military men, civilian politicians, diplomats, the emperor—put their country and its citizens in harm's way? Why did they make a decision that was doomed from the start? Introducing us to the doubters, bluffers, and schemers who led their nation into this conflagration, Hotta brilliantly shows us a Japan never before glimpsed—eager to avoid war but fraught with tensions with the West, blinded by traditional notions of pride and honor, nearly escaping disaster before it finally proved inevitable.